Improving English Speaking Ability Using Quantum Teaching Approach at Student Grade XI MAK of Ruhul Islam Anak Bangsa Islamic Boarding School - Riza, Muhammad (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2023)
This study aims to improve students' speaking abilities at the Ruhul Islam Anak Bangsa Islamic Boarding School in Aceh Besar through the Quantum Teaching approach. The research design was carried out in the form of classroom action research for 38 students of grade XI MAK. In this research, the teacher became a collaborator who carried out learning designed by researchers to be implemented in the classroom, and the researcher was an observer and fully responsible for this action research. The data in this research was collected through observation techniques on the students involved in learning. The obtained data were then analyzed using the average formula to measure individual student mastery. Meanwhile, data to see mastery in a classical manner was processed using the percentage formula. The research results show that the Quantum Teaching approach improves students' speaking skills. It can be seen from the average speaking skill of grade IX MAK students in Ruhul Islam Anak Bangsa Islamic Boarding School increased; in cycle I to 2.78, cycle II to 2.91, and cycle III to 3.45. Furthermore, the researcher or other teachers are expected to continue this research to obtain more significant findings on improving students' speaking skills.